Simultaneous presentation of parathyroid adenoma and papillary and medullary thyroid carcinoma - Luis R. Albavera-Giles; Juan G. Jurado-Reyes; Claudia I. Pérez-Álvarez; Zuri A. Irigoyen-Deseuza; Guillermo Castellanos; Yareli Melo (Revista Mexicana de Endocrinología, Metabolismo y Nutrición)
The association between parathyroid adenoma with papillary thyroid carcinoma (PTC) and medullary thyroid carcinoma is infrequent, and few cases have been documented. The diagnosis should be considered for the prevention of repeat surgery. We report the case of an 88-year-old male with a history of nephrolithiasis and bone pain. Laboratories showed a classic pattern of primary hyperparathyroidism. On evaluation, thyroid nodules (one of them with a fine needle aspiration report of Bethesda IV) were found, indicating parathyroid and thyroid surgery. Histopathology findings reported medullary and PTC and a parathyroid adenoma.